Method for monitoring intertidal communities in a steep rocky shore: a combination of digital image technology and field operational strategy (Brazilian Journal of Oceanography, 2007)
This paper introduces a method for temporal studies of steep rocky intertidal communities. It combines the use of digital image technology with field methodology, so that a wide area of the community can be sampled in a short time. Two current nondestructive percent cover estimation methods (visual estimation and point intersection) were compared in terms of cost, operational advantages and data quality, with a proposed method for a sucessional study . The proposed method used sequential photos to sample multiple fixed vertical transects over time. Reproduction of the mid-intertidal transect over time was possible by overlaying temporal transects in an image editing program. This method was similar to the point intersection quadrat method used to estimate percent cover. Benefits included reduced time on field work, economic advantages and other advantages of using digital photography, such as recording. Temporal photography of transects provided measurements of recruitment, mortality and population growth, and made it possible to manufacture an animation of sucessional stages. We suggest that this is the best method for providing information and understanding on the process of succession and for monitoring benthic invertebrate intertidal communities on steep rocky shores.